Патентно-ліцензійна політика як чинник інноваційної активності підприємства - Васильцова, Світлана Олександрівна (НТУ "ХПІ", 2018)
Подальша еволюція світової економіки тісно пов'язана з широким використанням інтелектуального ресурсу, в якому інтелектуальна власність в нинішньому тисячолітті буде основною рушійною силою. Тенденції створення цінностей свідчать, що найбільш динамічними галузями економіки є ті, які пов'язані з інтенсивною діяльністю у сфері знань та інтелектуальної власності. Ці тенденції показові не лише для майбутньої охорони інтелектуальної власності як стратегічного інструменту мікро- і макроекономіки, але також для характеру і видів інвестицій, які у недалекому майбутньому потрібно буде збільшувати для створення підґрунтя національному розвитку і підвищенн я актуальності інтелектуальної власності. У сучасних умовах права інтелектуальної власності та система їх захисту стимулюють глобальний інноваційний розвиток. Міжнародне визнання прав інтелектуальної власності можна розглядати як регулюючий механізм, що сприяє і забезпечує динамічну конкуренцію та торгівлю між країнами.

The further evolution of the world economy is closely linked to the widespread use of intellectual resources, in which intellectual property in the current millennium will be the main driving force. Trends in value creation indicate that the most dynamic sectors of the economy are those associated with intensive activities in the field of knowledge and intellectual property. These trends are indicative not only for the future protection of intellectual property as a strategic instrument of micro and macroeconomics, but also for the nature and types of investments that in the near future will need to be increased to create the groundwork for national development and increasing the relevance of intellectual property. In modern terms, intellectual property rights and their system of protection stimulates global innovation. International recognition of intellectual property rights can be seen as a regulatory mechanism that promotes and ensures dynamic competition and trade between countries. It is thanks to the procedure for the creation and protection of intellectual property of the country-producers of innovations have an additional incentive for the development of new technologies, and developing countries can actively implement them in production.
Patent-licensed policy as the factor of innovative activity of the enterprise
Keywords: патент; інтелектуальна власність; інновації; законодавство; intellectual property; legislation